Respuesta :

Answer:

A.   (f + g)(1) = - 9

B.    (f - g)(0) = -7

C.    (fg)(3) = 0

Step-by-step explanation:

A.    (f + g)(1) = f(1) + g(1)               f(1) = 1^2 - 9 = 1 - 9 = - 8       g(1) = 1 - 2 = - 1

                    = -8 -1 = -9

B.     (f - g)(0) = f(0) - g(0)             f(0) = 0^2 - 9 = 0 - 9 =  -9      g(0) = 0 - 2 = -2

                      =  -9 + 2 = -7

C.      (fg)(3) = f(3)(g(3)                   f(3) = 3^2 - 9 = 9 - 9 = 0    g(3) = 3 - 2 = 1

                    = 0(1) = 0